Installation of young farmers in the context of rural development in Romania: Implementation of action from the WWP aproach - Ignacio de los Ríos-Carmenado; Ramon Zamorano; Miguel Salvo; Pablo Rodriguez (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In the rural development context, the term Working With People (WWP) means a professional practice developed in cooperation that seeks to connect knowledge (expert and experienced) with actions by a common project. This professional practice includes the technical value of the production - goods and services generated - and incorporates the development of the actors who take part into the participatory activities. This communication illustrates the application from the USR (Support Unit of the National Network for Rural Development of Romania) of the WWP approach to the planning of measures addressed to Setting up of young farmers included in the National Rural Development Programme of Romania. Instruments used and results from the participatory activities, with planners, managers and direct beneficiaries, carried on by the USR are described. The results show the principal problems identified in Romania and the proposed improvements at the level of LAG, the USR and the Ministry of Agriculture. Participatory processes based on WWP approach allow the actors to be more than simple information providers, by involving them actively in the search of proposals of improvement. The integration of expert and experienced knowledge enables them to manage the implementation of the proposed solutions.
Keywords: 330; Working With People; young farmers; rural development